Sunlight‐Mediated Degradation of Polyethylene under the Synergy of Photothermal CH Activation and Modification. Issue 12 (8th November 2021) - Kong, Shengnan; He, Congze; Dong, Jin; Li, Ning; Xu, Chaoran; Pan, Xiangcheng
Abstract: The reuse of waste plastic has always been one of the challenges in the field of macromolecular science. The authors report that the degradation of polyethylene (PE) plastics can be achieved by a photothermal reaction using tetrabutylammonium decatungstate (TBADT) as photocatalysts, and the grafting of diisopropyl azodicarboxylate (DIAD) onto PE concurrently occurs under sunlight irradiation. Through adjusting the amount of DIAD or TBADT used in the reaction, low molecular weight PE waxes with tunable polarity can be prepared. This method can be applied to different sorts of PE plastics including films, gloves, and bags. Subsequently, synthesized low molecular weight PE‐ graft ‐DIAD waxes are used as compatibilizers to successfully realize the compatibilized blending of polyolefin plastics and starch, which paved a viable way to reuse waste plastics to reduce environmental pollution. Abstract : The low molecular weight polyethylene (PE) with tunable polarity is fabricated from waste plastics via photothermal reaction under sunlight, and the modified PE can be used as compatibilizers to blend polyolefin plastics and starch, which paves a new way for the recycling of waste plastics to reduce the pollution on the environment.